A Study of Thyroid Hormone Patterns in Patients with Acute and Chronic Liver Disease - Dr. Uppala Bhaskar Rao,; Dr Karri Anusha,; Dr Venkat Nikhil Adusumalli,; Dr Bhavani Mareedu, (International Journal of Pharma and Bio Sciences, 2023)
Thyroxine and tri-iodothyronine are essential for normal organ function, growth, and development. Thyroxine and tri-iodothyronine regulate the basal metabolic rate, which includes hepatocytes, thereby modulating liver function. The liver plays a vital role in the metabolism of thyroid hormones and the peripheral conversion of thyroxine to triiodothyronine by type 1 deiodinase. To date, some previous studies have shown that the most common change in the plasma level of thyroid hormones is a reduction in the total T3 and free T3 concentration associated with the severity of hepatic dysfunction. The current study aims to evaluate thyroid function in patients with acute and chronic liver diseases. Objectives of the study include assessing the severity of liver dysfunction in patients with hypothyroidism and hyperthyroidism. This prospective, hospital-based cross-sectional study was conducted in the inpatient department of General medicine from October 2019 to October 2021. A comprehensive physical examination was conducted, followed by a thorough review of their hospital records. Patients with acute hepatitis (acute onset of jaundice and three-fold rise in serum transaminases) and chronic liver disease (evidence of liver disease of more than 6 months’ duration and portal hypertension on ultrasonography or upper gastrointestinal endoscopy) were included in the study. Results showed a significant positive correlation between TSH and prothrombin time, child-pugh score, and total bilirubin. Total T3, free T3, and free T4 showed a significant positive correlation with albumin and a significant negative correlation with prothrombin time, child-pugh score, and total and direct bilirubin. So, thyroid hormone patterns may help assess the prognosis of patients with liver disorders as they show a significant correlation with established markers of prognosis of liver diseases.